Efeitos de diferentes tipos de estresse social sobre modelos animais de aprendizado, memória, ansiedade e depressão - Takatsu-Coleman, André Luis [UNIFESP] (2006)
The present study aimed to investigate the effects of two different social stressful procedures (social isolation and crowding) on behavioral parameters related to learning, memory, anxiety, depression and motor function. Mice were exposed to the above mentioned social stresses for different time periods and the behavioral parameters were simultaneously evaluated for each animal. In addition, plasma corticosterone levels were measured (in other animals) in an attempt to correlate them with the evaluated behavioral parameters, wich were quantified by the plus-maze discriminative avoidance task (learning, memory, anxiety, and motor function) and by the forced swim test (depressive-like behavior). Our results showed that acute exposure to both types of social stresses induced markedly distinct effects on behavioral parameters related to learning, anxiety, depression and motor function. Conversely, they produced the same effects (impairment) on memory parameters. Continued exposure to the social stress procedures employed led to tolerance of all the behavioral alterations, except social isolation-induced hyperactivity. Long-term exposure to either social isolation or crowding led to an identical pattern of behavioral effects: memory deficit, decreased anxiety level, depressive-like behavior and hyperlocomotion. These three latter behavioral effects may be related to an impulsivity enhancement. None of the behavioral effects induced by crowding was accompanied by modifications in plasma corticosterone levels. Conversely, bi-directional alterations in corticosterone levels were observed in social isolated mice (increase, tolerance and decrease in the levels were verified during progressive time exposure). Plasma corticosterone levels were considerably correlated with depressive-like behavior in social isolated mice. In addition, acute social isolation-induced depressive-like behavior was abolished by metyrapone (a drug that inhibits the synthesis of corticosterone) and induced by corticosterone injection. No other evidence of correlation was verified among the other behavioral parameters.